2012
DOI: 10.2174/138945012800675650
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Dependent Multivitamin Transporter (SMVT): A Potential Target for Drug Delivery

Abstract: Sodium dependent multivitamin transporter (SMVT; product of the SLC5A6 gene) is an important transmembrane protein responsible for translocation of vitamins and other essential cofactors such as biotin, pantothenic acid and lipoic acid. Hydropathy plot (Kyte-Dolittle algorithm) revealed that human SMVT protein consists of 635 amino acids and 12 transmembrane domains with both amino and carboxyl termini oriented towards the cytoplasm. SMVT is expressed in various tissues such as placenta, intestine, brain, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 70 publications
1
53
0
Order By: Relevance
“…Nanoparticles based on N-palmitoyl chitosan (DCX-NPa) exhibited an average hydrodynamic size of 429 ± 3.24 nm, with a polydispersity index of 0.398 and a positive Zeta potential value (+12.1 mV ± 0.38). These results are in good agreement with other reports concerning the fact that drug entrapment could induce a slightly increase of nanoparticles size (Vadlapudi et al, 2012;Jain et al, 2014) and positive Zeta potential values are given by the amount of non-substituted amino groups (Larsson et al, 2013). It has been reported that positive charged nanoparticles are able to induce cytotoxic effects and disruption of the cell membrane and seemed to be slightly more effective than anionic charged ones, even though both types of charged nanocarriers accumulated to a higher extent in tumor tissue compared with nonionic coated nanoparticles (Fröhlich, 2012).…”
Section: Particles Morphology Average Size and Surface Chargesupporting
confidence: 93%
See 1 more Smart Citation
“…Nanoparticles based on N-palmitoyl chitosan (DCX-NPa) exhibited an average hydrodynamic size of 429 ± 3.24 nm, with a polydispersity index of 0.398 and a positive Zeta potential value (+12.1 mV ± 0.38). These results are in good agreement with other reports concerning the fact that drug entrapment could induce a slightly increase of nanoparticles size (Vadlapudi et al, 2012;Jain et al, 2014) and positive Zeta potential values are given by the amount of non-substituted amino groups (Larsson et al, 2013). It has been reported that positive charged nanoparticles are able to induce cytotoxic effects and disruption of the cell membrane and seemed to be slightly more effective than anionic charged ones, even though both types of charged nanocarriers accumulated to a higher extent in tumor tissue compared with nonionic coated nanoparticles (Fröhlich, 2012).…”
Section: Particles Morphology Average Size and Surface Chargesupporting
confidence: 93%
“…In this regard, a series of small compounds with targeting functions such as: folic acid (Wang et al, 2011), arginine-glycineaspartic acid (Zhao and Zhai, 2013) and biotin (Yang et al, 2014;Zhu et al, 2015) have been widely used as a tumor targeting approach for anti-cancer drugs. Among all, biotin (vitamin B7 or H) is known to be involved in various cellular functions such as: cell growth or signal transduction (Vadlapudi et al, 2012). Furthermore, recent studies revealed that overexpression of biotin receptors on the surface of tumoral cells, especially breast cancer cells (Yang et al, 2009) can modulate the uptaken of biotinylated systems through a receptor-mediated endocytosis mechanism (Heo et al, 2012;Bu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Small molecule in vitro permeability and transporter assay platforms are largely applicable to study peptide permeability and transporter characteristics, such as log D (16,24), parallel artificial membrane permeability assay (PAMPA) (13,25), Madin-Darby canine kidney (MDCK) (26,27), Caco-2 (28-30), PEPT1 (31)(32)(33), and SMVT (34). The Caco-2 cell line possesses many of the human intestinal transporters (e.g., PEPT1, SMVT) and can be used to identify peptides with high absorption potential not only by transcellular or paracellular passive diffusion mechanisms but also by active uptake processes (30).…”
Section: Permeability Methods For Peptidesmentioning
confidence: 99%
“…Sodium-dependent multivitamin transporter (SMVT) is an important transmembrane protein responsible for translocation of vitamins and other essential cofactors such as biotin, pantothenate and lipoate [81]. SMVT is an electrogenic, highly sodium-dependent carrier-mediated system.…”
Section: Sodium-dependent Multivitamin Transportermentioning
confidence: 99%
“…A hydropathy plot (algorithm of Kyte and Doolittle) reveals that the human SMVT (hSMVT) protein (68.6 kDa) consists of 635 amino acids and 12 transmembrane domains with both N-and C-termini oriented towards the cytoplasm (intracellular region) (Figure 2.5a, b) [82][83][84]. Despite current knowledge of cell biology, molecular identity and regulation of SMVT carrier system, structure-function and structure-regulatory relationships are not fully known [81,83,85,86].…”
Section: Sodium-dependent Multivitamin Transportermentioning
confidence: 99%